O povo e a corrupção da República : um estudo sobre os limites da ação política republicana nos escritos de Maquiavel - Ivan Boato de Miranda (2021)
Our study presents an understanding of the limits of republican political action from an approach to the phenomenon of corruption in republics from the popular point of view. The strategy for the development of the theme consists of following the evolution of the freedom-tyranny dichotomy in the first eighteen chapters of the first book of Discourses on Livy of Machiavelli (chapters that present, according to many commentators, a great internal unity). We analyze and highlight the way in which the people get involved, either in the foundation and maintenance of freedom or in the advancement of the corruption process that ends up resulting in tyranny. We note and understand the fundamental importance of the desire for freedom for the possibility of the existence of a republic, which suggests that the problem of republican corruption must be inextricably linked to the demise of popular virtù within the political body. From this, we can say that the most appropriate analytical point of view to assess the degree of corruption of a given republic is the study of the virtù of the people of that republic.